STRATEGI PIMPINAN DALAM PENINGKATAN BUDAYA KERJA DOSEN DI PERGURUAN TINGGI - Noer Rahmah (LP3M IAI Al-Qolam Malang, 2016)
Universities as higher education are dominant social institutions that influence culture and responsible for cultural transmission and preservation. Higher education should be ready to face the challenges of globalization and must produce competitive graduates in the global era. Higher Education must have a global vision as well as employ international standard Resources. Therefore, mindset shift in universities is necessary to keep pace with the change andto create dynamic, productive, as well as competitive work culture. The followings are the strategies that can be taken by the university leaders in order to increase the lecturers’ work culture: (1) Creating the organizational and the intelligent culture; (2) encouraging the spirit of competition dynamic; (3) improvingemotional intelligence to establish effective network; and (4) intensifying communication to create cohesive work team. Keywords: Strategy, higher education, work culture